Harga Diri dan Kebersyukuran Sebagai Prediktor Citra Tubuh pada Remaja Perempuan Penggemar K-pop - Shabira, Fadzila; Uyun, Qurotul (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2023)
Usually, teenagers want to have a body that suits the beauty standard established by the media and society, which causes bad body image. There are several factors that can affect someone’s body image, two of them are self-esteem and gratitude. The aim of this research is to find out whether self-esteem and gratitude can predict body image on K-pop teenage fangirl or not. The hypothesis proposed in this research is self-esteem and gratitude could predict body image on K-pop teens fan girl, who often see idols as a benchmark for ideal body type. This research uses a quantitative approach, respondents involved in this research amounted to 607 K-pop teenage fan girl.  The measuring instrument used in this research are Multidimensional Body-Self Relations Questionnaire-Appearance Scale (MBSRQ-AS) by Cash dan Pruzinsky (2002), State Self-Esteem Scale (SSES) by Heatherton dan Polivy (1991) and Gratitude Questionnaire-6 (GQ-6) by McCullough et al. (2002). The result of this research indicates confirm with the proposed hypothesis, that self-esteem and gratitude could predict body image on K-pop teens fangirl. It shows that the values of R = .264 with a significance of p = .000 (p < .05) and value of R2 = .070, which shows that self-esteem and gratitude, together, can affect body image by 7% .